The concept of antagonistic metallic couples: a possible antidote for Alzheimer's - Shahab, Syed Alwi (2011)
The concept that there are naturally occuring antidotes to combat diverse forms of human physical illness has long enthralled the human imagination. The discovery of the existence of antagonistic (opposite) couples among the chemical elements in the periodic table has opened up a promising avenue for investigation into combating the onslaught of Alzheimer's disease and other illnesses involving toxic imbalance of chemical elements in the human body. There are also ramifications for applications in agronomy and water treatment.